Developing a theoretical success factor framework for the tendering phase of social infrastructure PPPs. Issue 6 (1st November 2020) - Simon, Laura; Jefferies, Marcus; Davis, Peter; Newaz, Mohammad Tanvi
Abstract: Australia's population is expected to grow from 24.6 million to 36.4 million inhabitants from 2017 to 2047. This is a challenge for providers of social infrastructure and requires an increase in the funding sources of both the public and private sectors. Simplifying private sector investment in Australia's infrastructure networks is essential. Public Private Partnerships (PPPs) allow the private sector to provide public infrastructure and any related services as well as opportunities for private investment or financing. The tendering phase of PPP projects is complex, long in duration and expensive and can have a negative impact on competition and Value for Money (VfM). This research summarizes a comprehensive literature review, including 67 references dated from 2003 to 2019, in order to identify, understand and classify the factors influencing the tendering process of social infrastructure PPPs. A theoretical success framework perceived through the lens of 'organization, process and people' is developed and focuses on the tendering phase. In each area, some factors have been identified that will enhance the possibility of a successful project tendering phase. The framework aims at decreasing complexity, length and cost of this key phase of the PPP life cycle and subsequently increase the overall project VfM.